Incidence, Treatment, and Survival Patterns for Sacral Chordoma in the United States, 1974–2011 - Yu, Esther; Koffer, Paul P.; DiPetrillo, Thomas A.; Kinsella, Timothy J. (Frontiers in Oncology, 2016)
Introduction Sacral chordomas represent one half of all chordomas, a rare neoplasm of notochordal remnants. Current NCCN guidelines recommend surgical resection with or without adjuvant radiotherapy, or definitive radiation for unresectable cases. Recent advances in radiation for chordomas include conformal photon and proton beam radiation. We investigated incidence, treatment, and survival outcomes to observe any trends in response to improvements in surgical and radiation techniques over a near 40 year time period. Materials and Methods 345 microscopically confirmed cases of sacral chordoma were identified between 1974 and 2011 from the Surveillance, Epidemiology, and End Results (SEER) program of the National Cancer Institute. Cases were divided into three cohorts by calendar year, 1974-1989, 1990-1999, and 2000-2011, as well as into two groups by age less than or equal to 65 versus greater than 65 to investigate trends over time and age via Chi-square analysis. Kaplan-Meier analyses were performed to determine effects of treatment on survival. Multivariate Cox regression analysis was performed to determine predictors of overall survival. Results 5-year overall survival for the entire cohort was 60.0%. Overall survival correlated significantly with treatment modality, with 44% surviving at 5 years with no treatment, 52% with radiation alone, 82% surgery alone, and 78% surgery and radiation (p<.001). Age greater than 65 was significantly associated with non-surgical management with radiation alone or no treatment (p<.001). Relatively fewer patients received radiation between 2000 and 2011 compared to prior time periods (p=.03) versus surgery, for which rates which did not vary significantly over time (p=.55). However, 5-year overall survival was not significantly different by time period. Age group and treatment modality were predictive for overall survival on multivariate analysis (p<.001). Conclusion Surgery remains an important component in the treatment of sacral chordomas in current practice. Fewer patients were treated with radiation more recently despite advances in photon and proton beam radiation. Overall survival remains unchanged. Additional analyses of margin status, radiation modality, and local control in current practice are warranted.